Intervention effect of ventilator‑assisted emergency endoscopy in the treatment of cirrhosis‑associated esophagogastric variceal bleeding - Xiu-Lian Wu; Yanmei Gu; Wenhui Wang; Jiayuan Wei; Xiaoqing Sun; Wenyue Hu; Wenhui He (Videosurgery and Other Miniinvasive Techniques)
Introduction: Emergency endoscopy has proven remarkably effective in the treatment of gastrointestinal bleeding. However, its efficacy has not been extensively evaluated specifically in patients with cirrhosis-associated esophagogastric variceal bleeding (EGVB). The patients may experience stress and anxiety before being subjected to the procedure.